2011
DOI: 10.1063/1.3615292
|View full text |Cite
|
Sign up to set email alerts
|

Combustion stabilization using serpentine plasma actuators

Abstract: This letter presents a numerical model for combustion stabilization with plasma actuators. Recently, we demonstrated that serpentine actuators induce complex neighboring flow structures due to pinching and spreading effects suitable for rapid flow mixing. Here, the influence of serpentine plasma actuator is numerically investigated on inner and outer recirculation zones of a gas turbine combustor. Beyond benchmarking with reported experimental data, we show that the swirl generated by the serpentine plasma act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…We believe that both serpentine and multi-barrier plasma actuators have numerous aerodynamic applications where an increased mixing of the local fluid is desired. The areas of boundary layer transition, convective heat transfer, and plasma assisted combustion (PAC) 23 all contain flow fields in which an improvement in flow turbulization could significantly enhance the desired output. An experimental study using a serpentine actuator on a freestream boundary layer of such an application remains open for evaluation in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that both serpentine and multi-barrier plasma actuators have numerous aerodynamic applications where an increased mixing of the local fluid is desired. The areas of boundary layer transition, convective heat transfer, and plasma assisted combustion (PAC) 23 all contain flow fields in which an improvement in flow turbulization could significantly enhance the desired output. An experimental study using a serpentine actuator on a freestream boundary layer of such an application remains open for evaluation in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…There has been significant research in this area for standard AC-DBD actuators at low speeds. [34][35][36][37][38][39][40][41] These studies have shown that 2D actuators create an out-of-plane velocity component that does not exist with 1D linear actuators. This out-of-plane velocity enhances mixing in the region which could prove useful for a number of applications e.g.…”
Section: Future Work On Ns-dbd'smentioning
confidence: 97%
“…In our prior study [12][13], we presented the serpentine actuator induced flow mixing on a flat surface and a gas turbine combustor. The results showed three-dimensional plasma effects extract momentum from an upstream flow injecting it into the bulk fluid through localized pinching and spreading effects.…”
Section: American Institute Of Aeronautics and Astronauticsmentioning
confidence: 99%